2006
DOI: 10.1080/02786820600796590
|View full text |Cite
|
Sign up to set email alerts
|

Ozone for Inactivation of Aerosolized Bacteriophages

Abstract: Because of increasing incidence of virus-containing aerosols, ozone was potentially considered to be a promising method to inactivate airborne viruses. In this investigation, bacteriophages MS2, phi X174, phi 6, and T7 are under evaluation. The effects of ozone concentration, contact time, different capsid architecture of virus and relative humidity (RH) on inactivating airborne viruses by ozone were evaluated in a laboratory test chamber. It was observed that the survival fraction of airborne virus decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
114
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(118 citation statements)
references
References 33 publications
4
114
0
Order By: Relevance
“…For cell-type bacteria, filtered E. coli cells were found to lose more than 70% of the colony after 1 h storage (Li and Lin 2001). Because a virus is more fragile than E. coli and yeast in terms of sampling stress in different samplers and inactivation by ultraviolet germicidal irradiation and ozone (Tseng and Li 2005a;Tseng and Li 2005b;Tseng and Li 2006), the effect of storage on filtered virus analyzed using the culture method should be much stronger than on virus analyzed using real-time qPCR. Therefore, the filter/real-time qPCR technique should successfully detect and quantify airborne influenza virus in field studies.…”
Section: Storage Effectmentioning
confidence: 99%
“…For cell-type bacteria, filtered E. coli cells were found to lose more than 70% of the colony after 1 h storage (Li and Lin 2001). Because a virus is more fragile than E. coli and yeast in terms of sampling stress in different samplers and inactivation by ultraviolet germicidal irradiation and ozone (Tseng and Li 2005a;Tseng and Li 2005b;Tseng and Li 2006), the effect of storage on filtered virus analyzed using the culture method should be much stronger than on virus analyzed using real-time qPCR. Therefore, the filter/real-time qPCR technique should successfully detect and quantify airborne influenza virus in field studies.…”
Section: Storage Effectmentioning
confidence: 99%
“…Wang (2003) found that low concentrations of ozone have high germicidal efficacy against Escherichia coli bioaerosols, but low germicidal efficacy for yeast bioaerosols in chamber studies. Klánová and Lajcíková (2005) indicated that the levels of Escherichia coli and Pseudomonas aeruginosa bioaerosols decreased to undetectable levels following ozone treatment for 12 h. Tseng (2006) found that ozone is highly effective in disinfecting four airborne viruses; however, viruses are generally difficult to treat with ozone because of their more complex capsid architectures and short contact time.…”
Section: Introductionmentioning
confidence: 99%
“…Many aerobiological technologies have been developed to control indoor bioaerosols: ventilation, filtration, ultraviolet germicidal irradiation, photocatalytic oxidation, ionization, ozone, negative ion, thermal disinfection (Christopher and Pasquale, 2002;Whitney et al, 2003;Kowalski, 2006;Tseng and Li, 2006;Yu et al, 2008;Yoosook et al, 2009). Ozone is a strong oxidant with a tremendous ability to oxidize odors, organic compounds, microorganisms, and other substances (Franken, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the reactive species in plasma, gas-based reactive plasmas are thought to be effective in killing various microorganisms (1)(2)(3). Therefore, recently, the inactivation of microorganisms in water by atmospheric-pressure cold plasmas (APCP) has attracted great attention for biomedical and environmental applications due to their lethal effects on bacteria and fungi (4)(5)(6)(7)(8), since APCP include many reactive species similar to those in the conventional methods of microorganism inactivation, such as ozone generation (9), UV irradiation (10), chemical agents (11), electrical fields (12,13), and microwave irradiation (14).…”
mentioning
confidence: 99%